Heterotopisk Svalbard-krim - Wærp, Lisbeth Pettersen (Nordlit, 2015)
How is the Arctic represented in modern crime fiction written by a female glaciologist, meterologist and polar explorer? Monica Kristensen is the author of a new, critically acclaimed, series of crime novels set in Svalbard. The first four novels of the series are Hollendergraven (2007, The Dutchman's Grave), Kullunge (2008, Coal Baby), Operasjon Fritham (2009, Operation Fritham), Den døde i Barentsburg (2011, The Dead Man in Barentsburg) and Ekspedisjonen (2014, The Expedition). According to the publisher, Forlaget Press, the series, when completed, will consist of altogether 12 books. The originality of the series is the use of Svalbard as setting. The setting is not only spectacular, it is significant: Knowledge of nature and climate is of greatest importance to the characters, the protagonist, police officer (sysselmannsbetjent) Knut Fjeld, as well as his various antagonists. Svalbard is not only a place in the Arctic, but also a group of islands. Both aspects are effectively exploited in Kristensen's novels. The representation of the Arctic archipelago is to a great extent based on the differences from other places, e.g. mainland Norway. The arcticle argues that the arctic archipelago as represented in these novels comes close to what French philosopher Michel Foucault calls heterotopia: A place that is totally different from other places, a place that represents the other, the deviant, and like the utopia and dystopia reflects the world of which it is an extension. Heterotopia is Foucault’s neologism (1967), and unlike the utopia/dystopia, the heterotopia actually exists. Within this theoretical framework the article presents a reading of the first five novels with special emphasis on the exploitation of place.